A Passion Denied - Lessman, Julie 1950- (Grand Rapids, MI : Revell, 2009)
Now that she has grown up, Elizabeth O'Connor wants more from her spiritual mentor, John Brady, than just his friendship and guidance, but John's past, with its horrifying secrets, will not allow him to return her love.
Keywords: Irish Americans -- Fiction; Sisters -- Fiction; Boston (Mass.) -- Fiction; United States -- Fiction -- History -- 1919-1933; Christian fiction; Love stories